Effectiveness of Myoinositol alone or in Companion with Metformin in Improving Hormonal, Metabolic, and Clinical Features of PCOS Women - Zainab Abdulhameed Alnisani; Manal Khaled Abdulrida (College of Pharmacy University of Baghdad, 2023)
Polycystic ovary syndrome (PCOS) referring to a syndrome that is recognized as a life-course disease and has both metabolic and reproductive signs; main pathophysiological cause includes insulin resistance, hyperandrogenism, and oxidative stress state. The study aimed to assess the impact of combining Myoinositol and Metformin, the main insulin-sensitizing drugs, on improving clinical, metabolic, and hormonal parameters in females with PCOS. A clinical trial that was prospective, randomized, and comparative on 54 patients (aged 18-40 y) are divided into three groups: group1 patients allocated to receive Myo-inositol(4g), group2 patients assigned to receive Metformin(1g) and group3 patients assigned to receive Myo-inositol(4g) + Metformin(1g) all for three months. Baseline and post-intervention fasting blood samples were collected to evaluate hormonal, metabolic parameters, and oxidative stress biomarkers.  Metformin and Myoinositol together lead to a significant drop free testosterone (P = 0.002), LH (P 0.003), LH to FSH ratio(P=0.004), FSI (P 0.012), the HOMA IR (p 0.019), hirsutism score (p=<0.001) and acne score (p= 0.003), besides substantial increase in GPX (P 0.02). Meanwhile, Myoinositol supplement causes a substantial drop in free testosterone (p=0.013), FSI (P 0.02), and HOMA - IR (P value=0.025) also a substantial rise in GPX (P=0.005).  Combining Myoinositol with metformin results in improving clinical, metabolic, hormonal parameters, as well as oxidative indicators for PCOS females.